2019
DOI: 10.1098/rspb.2018.2238
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of self-limited cell division of symbionts

Abstract: In mutualism between unicellular hosts and their endosymbionts, symbiont's cell division is often synchronized with its host's, ensuring the permanent relationship between endosymbionts and their hosts. The evolution of synchronized cell division thus has been considered to be an essential step in the evolutionary transition from symbionts to organelles. However, if symbionts would accelerate their cell division without regard for the synchronization with the host, they would proliferate more efficiently. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…If the host is in control of partner uptake, it can simply cease capturing new individuals [48]. Synchronized cell division can be selected for and is evolutionarily stable if symbionts can limit their own cell division and if both parties' benefit is large, as some theoretical results show [158]. Alternatively, if the symbiont is constantly growing faster, which can be seen as parasitism, host might evolve to counter symbiont by faster digestion, leading to a coevolutionary arms race [158].…”
Section: Controlling the Symbiont Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…If the host is in control of partner uptake, it can simply cease capturing new individuals [48]. Synchronized cell division can be selected for and is evolutionarily stable if symbionts can limit their own cell division and if both parties' benefit is large, as some theoretical results show [158]. Alternatively, if the symbiont is constantly growing faster, which can be seen as parasitism, host might evolve to counter symbiont by faster digestion, leading to a coevolutionary arms race [158].…”
Section: Controlling the Symbiont Populationmentioning
confidence: 99%
“…Synchronized cell division can be selected for and is evolutionarily stable if symbionts can limit their own cell division and if both parties' benefit is large, as some theoretical results show [158]. Alternatively, if the symbiont is constantly growing faster, which can be seen as parasitism, host might evolve to counter symbiont by faster digestion, leading to a coevolutionary arms race [158]. While both are costly processes, controlled lysis (digestion) may return some benefit by salvaging the eliminated partner.…”
Section: Controlling the Symbiont Populationmentioning
confidence: 99%
“…A particularly pertinent question is how host–endosymbiont relationships can become more intertwined, leading to a greater reliance on vertical rather than horizontal transmission. One model tackling this issue revealed that self-regulation would only evolve if the benefits of the relationship are sufficiently high for both the host and endosymbiont [ 45 ]. Analysis of the model also provided an explanation as to why benefits to both were necessary: when the benefit to hosts is large, then those without endosymbionts are outcompeted and lost in the population.…”
Section: Introductionmentioning
confidence: 99%
“…From the evolutionary perspective, it is likely that the early eukaryote contained a single mitochondrion that divided in synchrony with the cell as often observed for the bacterial endosymbionts of current eukaryotes [ 9 ]. Some eukaryotes have preserved this original blueprint of a single mitochondrion [ 10 13 ] which divides in synchrony with the entire cell.…”
Section: Introductionmentioning
confidence: 99%